Hermeneutic Interpretation of Confucian Wisdom in 孔子说 Kǒngzǐ Shuō: Philosophical Study and Contemporary Relevance - Usadani, Galuh Bunga; Muyassaroh, Lukluk Ul; Putri, Amira Eza Febrian; Firdaus, Dhevy Olivia; Octavia, Nurila Shanti (Universitas Cokroaminoto Palopo, 2025)
This study explores the philosophical and contemporary relevance of Confucian ethics through a hermeneutic interpretation of Shen Qiguo’s Kǒngzǐ Shuō: Nǐhǎo! (孔子说：你好！). Employing a qualitative philosophical–hermeneutic method, the research examines nine quotations reflecting the five Confucian virtues—仁 (Ren, humanity), 义 (Yi, righteousness), 礼 (Li, propriety), 智 (Zhi, wisdom), and 信 (Xin, integrity)—and focuses in depth on four key quotations: empathy (Ren), filial devotion (Li), learning (Zhi), and self-reflection (Yi/Zhi). Each quotation is analyzed through three interpretive stages: historical understanding, dialogical interpretation, and contemporary relevance. The findings reveal that these maxims form a cyclical ethical structure where empathy nurtures devotion, devotion fosters humility in learning, and learning culminates in self-reflection, which in turn reinforces empathy. This ethical circle demonstrates that Confucian values are dynamic, dialogical, and adaptable to modern contexts such as education, character formation, professional ethics, and organizational culture. The study highlights how hermeneutic engagement with classical Chinese philosophy can provide culturally grounded insights for contemporary moral education and leadership development.